AB0441 Using of subcutaneous methotrexate in aged patients with seropositive ra. (15th June 2017) - Muraviev, Y; Gridneva, G; Luchikhina, E; Demidova, N; Lebedeva, V; Karateev, D
Abstract : Background: Increasing life expectancy is a global process involving multiple nations, thus deeper insights into methotrexate (MTX) therapeutic potential in aged people is of paramount importance, as MTX still remains an anchor DMARD in RA management. Objectives: To assess the results of 12-months therapy with subcutaneous MTX (SC MTX) injections in RA patients aged more than 60 years. Methods: The 12 months open study included pts with active RA (DAS28 >3, 2), meeting ACR/EULAR (or ACR 1987) criteria, with RA lasting up to 3 years, and naïve to SC MTX. All pts were RF and/or ACPA-positive, 68% had increased BMI, 31% - obesity, 8% were smokers, 25% were taking oral GCS (≤10 mg/day equivalent to prednisolone ).All pts were administered SC MTX monotherapy once a week as a DMARD, starting at 10–15 mg/week, with subsequent 5 mg up-titration each 1–2 weeks (to max 30 mg/week) up to achieving the target (remission or minimum disease activity) or up to emergence of an adverse drug reaction (ADR). Folic acid (min 5 mg/week) was administered at any day(s) except for the day of SC MTX injection for ADR prophylaxis. Disease activity was scored using DAS28. GEBA were administered in pts with insufficient SC MTX clinical effect. Pts were monitored within universal institutional REMARKA program, envisaging physical examination, blood analysis and biochemistry panel (including liver enzymes and creatinine). STATISTICA 10 software was used for data processing. Results: 32 RA pts (28 females, 4 males) were included (mean disease duration 12±10 months, mean age - 65, 7±4, 7 years, mean DAS28 score -5, 6±0, 9. Cumulative SCMT dose by the end of the study reached 264±180 mg). The therapeutic target (remission or minimum disease activity based on DAS28 score) was achieved in 20 pts receiving SCMT monotherpay, 12 pts required administration of GEBAs. Adverse drug reactions (ADRs) were documented in 10 pts, including cases of more than one ADR at a time: breast abscess (1), alopecia (2), diarrhea (2), skin rash (1), a metallic aftertaste (1), local post-injection reactions (1), nausea (2), elevation of liver enzymes (3), leucopenia (1), pneumonia (1). There were 5 cases of SC MTX monotherpay discontinuation (2 - temporary, and 3 - permanent). The majority of pts (88%) could manage self-injection without additional training or assistance from medical staff. Conclusions: 62, 5% of aged RA pts participating in the study managed to achieve the therapeutic target after 12 months of SC MT monotherapy, although 31% ADRs rate required temporary (2)/permanent (3) SCMT discontinuation. Disclosure of Interest: None declared